The Effectiveness of Intradermal Suture Technique on Hypertrophic Scar Prevention in Rats - Wihastyoko, Herman Yosef Limpat; Wuryanjono, Wicaksono Patria (Lingkar Studi Bedah Plastik Foundation, 2022)
Introduction : Hypertrophic scarring is a complication that occurs in post-surgical wounds. There are many ways to prevent scarring, but there have been no satisfactory methods yet. Moreover, no studies investigated the effectiveness of intradermal sutures. Polypropylene thread can be used to repair a scar after surgery. This study aimed to prove the effectiveness of intradermal sutures using polypropylene thread on surgical scar quality.Method : The study was conducted using a randomized, controlled trial, and post-test only with 20 rats (Rattus norvegicus) as animal subjects. The wounds were made on the back, approximately 6 mm x 2 cm. Then, the rats were divided into two groups: a control group without intradermal sutures (K) and treatment group with intradermal sutures (I). Histopathological examination using Hematoxylin and Eosin (H&E) staining was used to identify the fibroblast number on the 21st day. The fibrocytes number were also observed on the 12th week and the Vancouver Scar Scale (VSS) was used to assess the scar quality.Result : The number of fibroblasts and fibrocytes in the control group (K) was significantly smaller (53.60 ± 14.571; 3.20 ± 0.447) than the treatment (I) (243.20 ± 75.334; 171.40 ± 13.221). The VSS value was significantly greater in the control than the treatment.Conclusion: The intradermal sutures using polypropylene thread produced a better-quality scar after surgery compared to wounds without intradermal sutures.